Requirement of different nutrients for yield maximization of Bt Brinjal (Bangladesh Journal of Agricultural Research, 2020)
The experiment was conducted at Agronomy field of Bangladesh Agricultural Research Institute, Gazipur during 2016-2017 and 2017-2018 to determine the nutrient requirement for yield maximization of Bt brinjal (var. BARI Bt Begun-2). The treatments were T1= STB (soil test base) recommendation (120-36-90-15-2-1 kg/ha N-P-K-S-Zn-B+ 3 t/ha poultry manure), T2 = T1 + 25% of N-P-K-S-Zn-B (150-45-112-18-2.5-1.25 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure), T3= T1 + 50% of N-P-K-S-Zn-B (180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure), T4= T1 + 25% of N-P-K-S-Zn-B + 3 t/ha poultry manure (150-45-112-18-2.5-1.25 kg/ha N-P-K-S-Zn-B+6 t/ha poultry manure), T5= T1 + 3 t/ha poultry manure (120-36-90-15-2-1 kg/ha N-P-K-S-Zn-B + 6 t/ha poultry manure). Nutrient uptake, yield components and yield of Bt brinjal varied significantly due to variation of nutrients in the tested years. The highest plant height (98-116 cm), canopy coverage (1.21-1.26 m2/plant), number of fruits/plant (57.69-59.23) and individual fruit weight (83-86 g) were obtained from 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure (T3) treatment where days to flowering showed the lowest values (109-110 days). The highest pooled yield (58.46 t/ha) of Bt brinjal was observed from the treatment 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B +3 t/ha poultry manure(T3) and the lowest (23.39 t/ha) from 120-36-90-15-2-1 kg/ha N-P-K-S-Zn-B+ 3 t/ha poultry manure) (T1). The highest nutrient uptake (214-43-208-60-0.38-0.213-49 kg/ha N-P-K-S-B-Ca) was also observed from the same treatment (T3). Fruit yield showed a strong (r=0.97) linear relationship with applied nutrients. Effect of nutrient application on fruit yield of Bt brinjal was estimated about 86%. The highest gross return (Tk. 587900/ha), gross margin (Tk. 417660/ha) and benefit cost ratio (3.45) were obtained by applying 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B+3 t/ha poultry manure. Results revealed that application of 180-54-135-22-3-1.50 kg/ha N-P-K-S-Zn-B along with 3 t/ha poultry manure would be economically optimum for achieving higher yield of Bt brinjal grown under Grey Terrace soil (Aeric Albaquept) of Gazipur.Bangladesh J. Agril. Res. 44(4): 591-598, December 2019